2019
DOI: 10.1101/847566
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meta-control of the exploration-exploitation dilemma emerges from probabilistic inference over a hierarchy of time scales

Abstract: Cognitive control is typically understood as a set of mechanisms which enable humans to reach goals that require integrating the consequences of actions over longer time scales. Importantly, using routine beheavior or making choices beneficial only at a short time scales would prevent one from attaining these goals. During the past two decades, researchers have proposed various computational cognitive models that successfully account for behaviour related to cognitive control in a wide range of laboratory task… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…A couple of studies that examined the influence of forced-choice task switching on voluntary task switches, found that increasing the proportion of forced choices, in particular in combination with high switch rates, increases voluntary task switching rates (Chiu et al, 2020;Fröber & Dreisbach, 2017). Taken together, this suggests that in conditions where experience is used to learn task models (Niv, 2019), meta-flexibility may be achieved by altering one's updating threshold or the rate at which this threshold is reached (both would be observed as a change in learning rate in RL modeling), which in turn may promote transferable effects (Goschke, 2003;Marković et al, 2019), as observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A couple of studies that examined the influence of forced-choice task switching on voluntary task switches, found that increasing the proportion of forced choices, in particular in combination with high switch rates, increases voluntary task switching rates (Chiu et al, 2020;Fröber & Dreisbach, 2017). Taken together, this suggests that in conditions where experience is used to learn task models (Niv, 2019), meta-flexibility may be achieved by altering one's updating threshold or the rate at which this threshold is reached (both would be observed as a change in learning rate in RL modeling), which in turn may promote transferable effects (Goschke, 2003;Marković et al, 2019), as observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous work within the domain of cognitive psychology has not drawn a sharp line between Online Supplementary Material can be found at: https://osf.io/bm6ps/. We made our data, material, and code (licensed under a Creative Commons Attribution-NonCommercial 4.0 International License) available at: https://osf.io/skh5y/ exploration-exploitation on the one hand and flexibilitypersistence on the other (Hills, 2006;Hills & Dukas, 2012;Hommel & Colzato, 2017;Marković et al, 2019). For instance, and among others, Hills et al (2008Hills et al ( , 2010 have illustrated that such theoretical overlap is not far-fetched, because abstract conceptual search can be primed by inducing explorative or exploitative foraging strategies, with high levels of exploration (vs. exploitation) boosting flexible (vs. persistent) cognitive search patterns.…”
Section: Introductionmentioning
confidence: 99%
“…15 Feasible solutions of such metacontrol problems must therefore rely on learning processes that enable agents to infer from prior experience in which contexts it is adaptive (and maximizes reward in the long run) to stick to prior commitments and when it is more adaptive to adjust preferences more myopically in light of one's current motivational state. Initial computational-modeling studies indicate that experience-based learning in conjunction with Bayesian inference may provide a basis for solving such metacontrol problems (Markovic et al, 2021). However, we are not aware of any attempts to date to apply such models to the domain of self-control, and it will thus be a key challenge for theories favoring Resolution 3 to apply such models to preventive self-control and test them empirically.…”
Section: Evaluation Of Resolution 3: Nonsynchronous Self-controlmentioning
confidence: 99%